Belajar Dari Totalitas Pelayanan Daud Bagi Pelayanan Masa Kini - Riste Tioma Silaen; Sabudin Sabudin; Nurliani Siregar (STT Pelita Dunia, 2023)
Abstract: David continued to lead the people of Israel as a king after Saul. The appointment of David and the period of reigning Israel are interesting to explore from many fields for researchers. This paper aims to discuss David's performance as a servant with a position as a king from the point of view of the totality of self, energy, and mind for the advancement of God's kingdom in the world. The researcher used a descriptive qualitative method from related selected literature sources. The data are sorted and reduced according to the research objectives to obtain a synthesis that supports the ideas in the conclusion section. David's whole life in God was evident from his works as a shepherd (1 Sam. 16:20). David's totality was also seen when working for King Saul (2 Sam. 1-8), also when ruling as a King (2 Sam. 5-8). David showed totality in energy, mind, and all of which was adrift in the frame of fear of God. Abstrak: Daud melanjutkan tongkat pimpinan bagi rakyat Israel sebagai raja setelah Saul. Pengangkatan Daud dan masa memimpin Israel mempunyai daya tarik untuk ditelusuri dari banyak bidang bagi peneliti. Tulisan ini bertujuan mendiskusikan kinerja Daud sebagai seorang pelayan dengan posisi sebagai Raja, dari sudut totalitas diri, daya tenaga, pikiran untuk kemajuan kerajaan Allah di dunia. Peneliti menggunakan metode kualitatif deskriptif dengan perolehan data dari sumber literatur terkait yang dipilih. Data dipilah dan direduksi sesuai tujuan penelitian sehingga memperoleh sintesa yang mendukung gagasan pada bagian kesimpulan. Daud tampak total hidup dalam Tuhan terbukti sejak Bekerja Sebagai Gembala (1 Sam. 16:20). Totalitas Daud juga tampak ketika bekerja pada Raja Saul (2 Sam. 1-8), juga ketika memerintah sebagai Raja (2 Sam.5-8) Daud menunjukkan totalitas dalam tenaga, pikiran, yang semua terpaut dalam bingkai Takut pada Allah.